Aplikasi Sistem Ujian Berbasis Web dan Mobile Pada SMK Perintis Kabupaten Bandung Provinsi Jawa Barat - Uddin, Badie; Azis, Idris Abdul; Dhika, Harry; Liani, Noval (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The Mid-Semester Examination (UTS) and Final Semester Examination (UAS) at Perintis Vocational School are still carried out manually. To familiarize students and teachers in facing the Computer-Based National Examination (UNBK) held by the Department of Education and in order to participate in implementing the government’s Go Green program, one of which is limiting/reducing the use of paper (paperless), it is necessary to have an application that can fulfill the activities such as UTS and UAS which adopt the UNBK application system. The application was developed using a System Development Life Cycle (SDLC) approach using the waterfall model and using the PHP and HTML programming languages, and the database used MySQL. The tools and editors used are Sublime and Android Studio. The web-based exam application can be accessed by admins and teachers via PC/laptop, while the mobile-based exam application can only be accessed by all students via smartphones with the Android operating system..